Filipe Lucio speaks about the objectives of the Global Framework for Climate Services Program - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Filipe Lucio, Director of the Global Framework for Climate Services at the World Meteorological Organisation speaks about the objectives of the programme. He was speaking during a consultative meeting between users and providers of climate services in Tanzania in May 2014.